Effect of using slender flanges on EN 1993-1-5 design model of mono-symmetric S460 corrugated web bridge girders. (October 2021) - Hassanein, M.F.; Elkawas, A.A.; Bock, Marina; Shao, Yong-Bo; Elchalakani, M.
Abstract: Eurocode (EC3) bending moment design model of mono-symmetric corrugated web girders (CWGs) is based on the critical failure mode among the tension flange yielding, the compression flange yielding and the lateral-torsional buckling (LTB) of the compression flange. Recently, LTB behaviour of S460 laterally-unrestrained mono-symmetric CWGs with fully-effective flanges has been investigated by the authors, from which EC3 design model has been modified to better represent their actual strength. Nevertheless, the effect of the local buckling (LB) of slender compression flanges on the flexural strength and behaviour of such long girders has not been examined. While the corrugated web potentially makes large contribution to the out-of-plane stiffness, LB of the compression flange is expected to reduce LTB resistance of such girder significantly. Principally, this paper is devoted to exploring such effect on the accuracy of EC3 bending moment design model. Currently, virtual tests, by using ABAQUS software, are generated based on accurate validation. Then, parametric studies, intentionally designed to eliminate the tension flange yielding, are carried out on simply supported girders considering mainly the influences of the flange and web dimensions on the behaviour of S460 mono-symmetric CWGs. The strengths of such girders are compared with EC3 design model, from which it is found to provide unsuitable predictions. Hence, new formula has been proposed to accord better with the FE results. Additionally, several conclusions are provided at the end to assist design engineers in suggesting efficient cross-sections.